Separately continuous mappings with values in nonlocally convex spaces - Karlova, O. O.; Maslyuchenko, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We prove that the collection $(X, Y, Z)$ is the Lebesgue triple if $X$ is a metrizable space, $Y$ is a perfectly normal space, and $Z$ is a strongly $σ$-metrizable topological vector space with stratification$(Z_m)^{∞}_{m=1}$, where, for every $m \in \mathbb{N}$, $Z_m$ is a closed metrizable separable subspace of $Z$ arcwise connected and locally arcwise connected.